Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan - Purwanto, Edi; Muhtadin, Imam; Amalia, Liliyani Nur (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
ABSTRACT This research was conducted with the aim to test and analyze “The Effect of Leadership Style and Dicipline Work on Employee Performance in PT. Agung Rahardja Manunggal Yudha”. The analytical methods used include the validity test, the reliability test with the classic assumption test, multiple linear alaysis, and the coefficient of determination analysis to test and prove the hypothesis. The method of data collection in this study was done by distributing quesionnaires to 60 respondens. The research method used is an associative quantitative method using primary and secondary data. In this research, leadership style has a positive and significant effect agains employee performance. This can be seen from the value of tcount = 7,029 which is bigger than ttable = 2,003 or (7,029> 2,003) and the value of sig = 0,000 is smaller than = 0,05 or (0,000 < 0,05). Discipline work has no positive effect and non significant effect against employee performance. This can be seen from the value of tcount = 1,458 which is smaller than ttable = 2,003 or (1,458 < 2,003) and the value of sig = 0,150 is bigger than 0,05 or (0,150 < 0,05). Leadership and discipline work together have a positive and significant effect against employee performance. This can be proven from the value of Fcount = 108,309 which is bigger than Ftable = 3, 16 or (108,309 > 3, 16), and the value of sig = 0.000 is smaller than = 0.05 or (0.000 < 0.05). The result of this study, it can be proven that leadership style has a positive and significant effect against employee performance, while discipline work have no positive effect and non significant effect against employee performance, also leadership style and discipline work simultaneously have a positive and significant effect against employee performance. Keywords: Leadership Style, Dicipline Work, and Employee Performance